Addressing Climate Change Through a Low-Cost, High-Impact Carbon Tax. (March 2019) - Geroe, Steven
This article considers design features of a low-cost, high-impact carbon tax in terms of emissions reductions, drawing on international implementation experience. Costs can be reduced by offsetting carbon taxes with reductions in other taxes, using carbon tax revenue to compensate stakeholders, and incremental implementation. Impacts can be augmented by investing revenue in emissions reduction activity and complementary tax incentives for low-emissions technologies. Jurisdictions that have implemented such carbon taxes have continued to experience strong economic growth. While revenue and distributionally neutral carbon taxes that do not increase the overall tax take or change the distribution of wealth have been effectively introduced in many jurisdictions, this has not been the only approach. The more fundamental conclusion is that carbon taxes are being designed to maximize political acceptability and minimize economic disruption in their implementation context. This evidence of convergence toward low-cost, high-impact carbon tax design elements is establishing a viable pathway for international cooperation on carbon pricing at levels adequate to address climate change. Conversely, recent French experience indicates that carbon tax increases not based on substantial revenue and distributional neutrality may not be viable.